Ta`līm al-Ḥiwār Bi at-Tamṡīl Li Tarqiyyah Qudrah aṭ-Ṭalabah `Alā at-Takallum Bi al-Lughah al-`Arabiyyah (Dirāsah Tajrībiyyah Bi Ma`had Bāb an-Najāḥ al-`Aṣrī Banda Aceh) - Zikrullah Nuzuli; Azman Ismail (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2020)
The method of dialog (conversational Method) is one method of teaching foreign languages ​​such as Arabic, English, or other languages ​​by directly inviting students to dialogue/speak with the foreign language being taught. Playing drama is one way to make it easier for students to remember Arabic vocab. The conversational method intended here is a way of teaching by dramatizing behavior in the form of social relations. As for the problems that researchers encounter at the modern Babun Najah boarding school, some students at the Modern Pesantren Babun Najah are less able to understand the language when dialoguing with Arabic with their friends well and it is also difficult to pronounce the Arabic language. From these problems, the researcher wants to discuss research entitled "Muhadatsah Learning through the dramatization method to improve students' Ability to Engage in Dialogue using Arabic". The research method used by researchers in writing this thesis is a quasi-experiment, this method which launches the design of a study, which aims to examine the relationship of cause and effect to the cause of the phenomenon. The Mujtama' in this study were students of class 1 Aliyah Modern Islamic Boarding School Babun Najah Ulee Kareng where students numbered 151 people, and the sample was class 1 MIA 4 students, amounting to 32 people, viewed from the learning aspects and the results of research has been done on that class is increasing. The Muhadatsah learning through the method of dramatization can improve students' ability in dialogue by using the Arabic language because it can be seen through the value of to and it is clear that the value of 22.03% is higher than the percentage value of 5% = 2.04 and 1% 2.75. While the motivation of students in dialogue by using drama achieves excellent value categories.